Short-run price and income elasticity of gasoline demand - Marrouch, Walid (2012)
We empirically estimate the demand for gasoline in the presence of multiple shifts caused by structural breaks using monthly data from Lebanon covering the period 2000:M1–2010:M12. Consistent with most studies in the literature, our study reports that gasoline is price and income inelastic in the short-run. However, when a single and multiple breaks are introduced, the consumers’ responsiveness to gasoline price and income increase. Since both price and income elasticity are sensitive to structural changes, a policy that pleads for a flat excise tax may not be optimal with respect to either the cyclical pattern of government revenues or the internalization of international environment standards.